Membangun Harmoni Sosial: Kajian Sosiologi Agama tentang Kearifan Lokal sebagai Modal Dasar Harmoni Sosial - David Samiyono (JSW (Jurnal Sosiologi Walisongo), 2017)
Every ethnic in Indonesia have an unique local wisdom. This local wisdom is usually used to resolve any problems or conflicts. And most conflict that have happened in Indonesia is SARA. SARA is an acronym for suku (ethnict), agama (religion), ras (race), dan antar golongan (amongst group community). From social economic problem, cultural, religion, or even political problem such as election of head village and presidential election in Indonesia is related to SARA conflict. Local wisdom is every values, norms, rules, that live in society. This local wisdom binds people and become the way of life in society. This paper would try to contribute how local wisdom have significant role to build social harmony in society. And all datas that have been collected for this paper are the collection of research from all over Indonesia to build harmony based on local wisdom.